Analysis of switching and matching stubs in reconfigurable power divider with SPDT switch function - N. Edward; N. A. Shairi; Z. Zakaria; I. D. Saiful Bahri (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2019)
In this paper, performance analysis of switching and matching stubs was done to a reconfigurable power divider with Single Pole Double Throw (SPDT) switch function. Two designs (Design A and Design B) with different positions of switches and matching stubs were proposed. Rogers RO4350 (er=3.48, h=0.508 mm) was used in this analysis as a substrate material with copper thickness of 0.035 mm. The performance analysis was carried out based on insertion loss, return loss and isolation parameters. The simulated results showed that Design B had a better performance than Design A and was able to work as a reconfigurable power divider with SPDT switch function.